Hypoglossal Nerve Neuropathies—Analysis of Causes and Anatomical Background - Andrzej Węgiel; Nicol Zielinska; Mariola Głowacka; Łukasz Olewnik (Biomedicines, 2024)
The hypoglossal nerve is the last, and often neglected, cranial nerve. It is mainly responsible for motor innervation of the tongue and therefore the process of chewing and articulation. However, tumors, aneurysms, dissections, trauma, and various iatrogenic factors such as complications after surgeries, radiotherapy, or airway management can result in dysfunction. Correct differential diagnosis and suitable treatment require a thorough knowledge of the anatomical background of the region. This review presents the broad spectrum of hypoglossal neuropathies, paying particular attention to these with a compressive background. As many of these etiologies are not common and can be easily overlooked without prior preparation, it is important to have a comprehensive understanding of the special relations and characteristic traits of these medical conditions, as well as the most common concomitant disorders and morphological traits, influencing the clinical image. Due to the diverse etiology of hypoglossal neuropathies, specialists from many different medical branches might expect to encounter patients presenting such symptoms.